RESULTS OF INTRA-ARTICULAR HYALURONIC ACID INJECTION IN OSTEOARTHRITIS OF THE KNEE - Selçuk KESER; Ahmet BAYAR; İbrahim TUNCAY and Ahmet EGE and Nurettin DEMİREL (Archives of Rheumatology, 2004)
In this prospective study, the outcome of intraarticular hyaluronic acid injections in patients with gonarthrosis, that were classified according to radiologic grade, were analysed. Forty female patients with the diagnosis of gonarthrosis according to the criteria of American College of Rheumatology and with a mean age of 59 (40-73), were treated with weekly intraarticular injections of hyaluronic acid for three weeks. Radiologic assessment was made according to the Kellgren-Lawrence classification. The results were evaluated according to the values of visual analoque scale on walking painrest pain, patient satisfaction and the Lequesne Functional Index that were examined at baseline, 3rd and 6th months. Patients with grade I and II gonarthrosis had significantly decreased scores of walking pain, rest pain and Lequesne index at 3rd and 6th months (p<0.05). Seventy two percent of these patients were satisfied with the treatment. While the patients with grade III gonarthrosis also had significantly decreased scores of walking and rest pain at 3rd month (p<0.05), Lequesne index values were not significantly altered. The only significant difference at 6th month was the lowered resting pain. Sixty percent of grade III patients were satisfied with the treatment. Intraarticular hyaluronic acid injection is a useful medical treatment option for patients with radiologic grade I,II gonarthrosis. It may be used for palliative treatment of pain for patients with advanced age, grade III gonarthrosis and for those rejecting an operation.